An analysis of the export potential of the garment industry in Lao PDR : a case study of VM Inter Garment - Sengsaden Bounlavong; Swierczek, F.W.; Sununta Siengthai; Donyaprueth Krairit; Japan International Cooperation Agency (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
The Lao garment industry has been developing for more than 10 years. It started as an import substation, growing into the country's biggest foreign exchange earner. The industry is integrated with upstream industries, such as fiber manufacturing, intermediate industries, such as spinning, weaving and dyeing. The industry employs more than 20,000 people, SO percent of who are in the garment industry. This research study's main objectives are to analyze the present situation, opportunity and challenges to the Lao garment industry. In addition, this research will identify strategies of a Lao garment firm in order to acquire competitive advantages over the firm in local market. (Case Study: VM Inter Garment). The research also analyzes the SWOT analysis of a garment business: VM Inter Garment. The result shows even though Laos has a long history in the garment industry, Laos still has problems with low quality products because of obsolete technology and machines in the production process. In addition, there are problems with the scarcity of marketing strategies, low skills labor. Although, VM Inter Garment has gained its low tariff of raw material imported, but the cost of production and transfer to markets especially to EU market is still high. The research is also shown that Lao garment industry should manufacture higher quality products and apply the supply chain system in production process in order to compete with the high quality product countries such as Thailand, Hong kong, and Taiwan. At the same time, the government should be well prepared for the garment industry under free trade regime, through an improvement skill labor, and the product standard
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2006
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Keywords: Clothing trade -- Laos; Exports -- Laos